2020
DOI: 10.2147/ott.s237162
|View full text |Cite
|
Sign up to set email alerts
|

<p>IFI30 Is a Novel Immune-Related Target with Predicting Value of Prognosis and Treatment Response in Glioblastoma</p>

Abstract: As a crucial part of anti-tumor immunotherapy, interferon-α/β (IFN-α/β) treatment has been broadly applied to clinical trials of glioma. However, less is known about implement of interferon-γ (IFN-γ) in glioma. Further investigating the valuable hub molecular of IFN-γ family might provide us a novel guidance for glioma therapy. Methods: This study carried out an analysis on glioma patients from the Chinese Glioma Genome Atlas (CGGA) and The Cancer Genome Atlas (TCGA) cohorts. The analyses were performed by Gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…Among them, DCBLD2 [ 26 ], FNDC3B [ 27 ], PLP2 [ 28 ], SERPINH1 [ 29 , 30 ], STEAP1 [ 31 , 32 ], and TNFRSF1A [ 33 ] were found to be abnormally expressed in a series of human tumors. IFI30 is the most stable prognostic gene among interferon-stimulated genes in glioma[ 34 ]. CFI is a potential therapeutic target for nonmelanoma skin cancer[ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, DCBLD2 [ 26 ], FNDC3B [ 27 ], PLP2 [ 28 ], SERPINH1 [ 29 , 30 ], STEAP1 [ 31 , 32 ], and TNFRSF1A [ 33 ] were found to be abnormally expressed in a series of human tumors. IFI30 is the most stable prognostic gene among interferon-stimulated genes in glioma[ 34 ]. CFI is a potential therapeutic target for nonmelanoma skin cancer[ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It plays a significant role in regulating the transport of cholesterol through the late endosomal/lysosomal system in the past researches (Lauber et al, 2018;Liu et al, 2020). Its predicting value of prognosis and treatment response in glioblastoma as a novel immune-related target was also verified (Zhu et al, 2020).…”
Section: Discussionmentioning
confidence: 95%
“…After searching in Pubmed, we found that the expression and function of LSP1 ( Park et al, 2014 ), LY96 ( Rajaraman et al, 2009 ), IFI30 ( Liu et al, 2020 ; Zhu et al, 2020 ), and ARPC1B ( Lauber et al, 2018 ) in GBM has been reported, and research about NPC2 in GBM are remain rescue. Hence, we focus on investing the clinical prognostic significance of the NPC2 genes in GBM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IFI30 is highly expressed in glioma and associated with chemotherapy response ( Zhu et al, 2020 ). Our analysis showed that IFI30 were specifically upregulated and this high expression predicted high RFS and OS ( p < 0.05) in Her2-subtype breast cancer, while high IFI30 expression predicted low RFS and OS ( p < 0.05) in all breast cancer.…”
Section: Discussionmentioning
confidence: 99%